Immunization in pregnancy safety surveillance in low and middle-income countries- field performance and validation of novel case definitions. Issue 22 (16th May 2019) - Kochhar, Sonali; Clarke, Ed; Izu, Alane; Emmanuel Kekane – Mochwari, Kebonethebe; Cutland, Clare L.
Abstract: Background: A globally standardized approach in high and low and middle-income countries (LMIC) to actively monitor the safety of vaccines for pregnant women during development and implementation phases is critical. Brighton Collaboration's (BC) Global Alignment of Immunization Safety Assessment in Pregnancy (GAIA) project has developed globally standardized case definitions (CDs) of key obstetric and neonatal terms for the assessment of safety of vaccines in pregnancy. CDs are categorized into levels of diagnostic certainty, facilitating their use in varied settings. This study evaluates the field performance of CDs in LMIC. Methods: Data from pregnant participants of RCTs for trivalent inactivated influenza vaccine conducted at Chris Hani Baragwanath Academic Hospital, South Africa (SA) between 2011 and 2013 were reviewed retrospectively for preterm birth, stillbirth and hypertension CDs and the Gestational age assessment (GA) algorithm. Data from an ongoing pneumococcal vaccine trial (conducted at MRC Unit, The Gambia) were collected prospectively for GA. Results: For GA, 600 mother-infant dyads from Gambia and 155 mother-infant dyads from SA were reviewed. Level 2B (unsure LMP and US in 2nd trimester) was the most common level seen in Gambia (63%) and level 3B1 (unsure LMP with physical examination) in SA (43%). Preterm deliveries had similar results in SA. The pregnancy-induced hypertension definition performed well, with 96% (54/56) of cases fulfilling 'level 1' for 'preeclampsia with severe features'. 24 stillbirths were identified and 21 records were reviewed; 73.3% (11/15) of the stillbirths classified as antepartum by attending physicians and 83.3% (5/6) of the intrapartum stillbirths did not fulfil the criteria for any level of certainty. Conclusion: BC CDs for neonatal and maternal outcomes (preterm and hypertension) and GA were sensitive, reliable and feasible to use in RCTs in SA and Gambia. Modifications to the stillbirth CD are required to improve its usefulness in varied settings.